Aplikasi Pengukuran Kekuatan dan Rekomendasi Password Berdasarkan Input Pengguna dengan Metode Entropi - Bacilius Agung Suburdjati; Fransiska Nindita Iswari; Wilson Kenneth Jonathan (LPPM Universitas Nias Raya, 2024)
This study develops a Python-based application to evaluate password strength and provide more secure password recommendations using the NATO phonetic alphabet, True Random Number Generator (TRNG), and Pseudorandom Number Generator (PRNG). The application aims to enhance user security by generating passwords with high entropy. This entropy is influenced by character variation, password length, and the combination of symbols, numbers, and letters. The study shows that the more complex a password is, the longer it takes to be cracked. However, overly complex passwords are often difficult to remember, requiring a solution that maintains security without compromising usability. The developed application not only measures password strength but also provides stronger password recommendations through three methods. The first method replaces some password characters with the NATO phonetic alphabet, making them easier to remember. The second method adds random characters based on PRNG, while the third method combines TRNG and NATO to enhance password complexity. With this approach, the application offers a practical solution to improving digital security, helping users create stronger passwords that remain easy to use in daily life.